The use of Oral Bovril as growth hormone stimulation test - Loh, Huai Heng; S , Norlela; Abd Wahab, Norasyikin; M, Norlaila; O, Mohd Rahman; R, Subashini; Shahar, Mohammad Arif; Omar, Ahmad Marzuki; WS, Wan Juani; M., Azura Dina; Ooi, CP; S, Muhammad; et al. (Malaysian Endocrine & Metabolic Society, 2014)
Introduction: The gold standard for diagnosing growth hormone deficiency is insulin tolerance test. However, this is contraindicated in patients at risk of seizure attacks. GHRH-arginine test is not widely available. The other tests have their own limitations. Oral Bovril contains arginine and can be used as a substitute when all others are not available. Case: A 16-year old boy with underlying mitochondrial disease, complicated with myoclonus and secondary hypogonadism, presented with short stature. Oral Bovril test was performed to rule out growth hormone deficiency as other tests were not available. Materials and Methods: Oral Bovril, given as 14g/m2 body surface area, was used in this patient (subject A) after an overnight fast. The test was also performed on a healthy sex-matched adult (subject B) and a sex and age-matched patient with confirmed growth hormone deficiency (subject C). Serial blood tests were taken at baseline and half hourly for 2.5 hours. Results: Subject A attained peak growth hormone of 28.4mIU/L which was consistent with a normal response, hence ruling out growth hormone deficiency. Subject B attained peak growth hormone of 42.0mIU/L. Subject C has suppressed growth hormone throughout the test, consistent with previous insulin tolerance test. Conclusion: Oral Bovril test is an option when all other growth hormone stimulation tests cannot be performed. It is cheap, readily available, has no side effects, does not require intravenous infusion, and has fairly good performance.